IoT4Fun: a relational model for hybrid gameplay interaction - ALBUQUERQUE, Anna Priscilla (2017)
Both toy and games industries are investing in hybrid play products. In such scenarios the user access the system using toys as input/output, thus, these products consist of playful user interfaces. Hybrid play systems are complex design artefacts since they use real and virtual information, so they present new challenges to both designers and developers. We suppose both industries could benefit with hybrid design approaches from product concepts. Our main research goal aims to develop tools and methods to assist the community in developing such interactions. Hence, we performed a systematic literature review covering related research published between 2008 and 2016. To extend our contribution, we added 120 hybrid play products from a market review. After data extraction, we managed results to propose a relational model for hybrid gameplay interaction. The model comprises several interactive aspects relating three entities: the things, environment, and people. The model allowed describing different scenarios of smart play including both active and passive technologies, that are located either in outdoor or indoor environments. Aiming to evaluate model usage, we applied it as a practical tool for designing hybrid playful systems. To achieve it, we included the model in a 16-week class to design hybrid games. We detailed model usage in the course schedule and discussed how students experienced it. Besides, we presented student’s six working prototypes, including design cycles, and playtesting sessions. After class, we conducted semi-structured interviews with student’s representatives. Results revealed model usefulness to describe their system setup and interface elements. According to students, model vocabulary facilitated communication among team members. Afterwards, we proposed improvements in model nomenclature based on student’s feedback. Thus, to evaluate changings we applied the model in a series of three creative workshops. Workshops had 4-8 hours of duration that focused on stages of conception, ideation, and lowfidelity prototyping. Accordingly, updated model enabled participants in developing six hybrid game concepts. Finally, we summarised research contributions and recommended topics for a future methodological approach